2012
DOI: 10.2174/1874216501206010034
|View full text |Cite
|
Sign up to set email alerts
|

GH in the Central Nervous System: Lessons from the Growth Hormone Receptor Knockout Mouse

Abstract: Various central nervous system (CNS) tissues express both growth hormone (GH) and its receptor (GHR), including those involved in memory and cognition. Studies show the presence of GHR in the pituitary, choroid plexus, hypothalamus, hippocampus, pituitary and the spinal cord during development and, to a lesser extent, in adults. This expression implies a role of GH signaling in growth, development and functionality of the CNS. While data on the function of GH in the CNS is sparse, several studies have been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Later, quantitative PCR and immune-histochemical studies confirmed a near ubiquitous expression of GHR throughout the brain of humans as well as rats and mice (reviewed in (253,254,255)). Particularly high expression levels of GHR was observed in the choroid plexus, pituitary, hippocampus, thalamus, and hypothalamus (256).…”
Section: Ghr Presence In Brainmentioning
confidence: 95%
See 1 more Smart Citation
“…Later, quantitative PCR and immune-histochemical studies confirmed a near ubiquitous expression of GHR throughout the brain of humans as well as rats and mice (reviewed in (253,254,255)). Particularly high expression levels of GHR was observed in the choroid plexus, pituitary, hippocampus, thalamus, and hypothalamus (256).…”
Section: Ghr Presence In Brainmentioning
confidence: 95%
“…The apparent dichotomy in the patterns of GH action in affecting cognition and memory is reflected in the decreased brain size in bGH mice and increased brain size in GHA and GHRKO animals relative to total body weight although the rest of the body parts show a more proportionate variation (253). However, no difference in total cell number was reported in the embryonal central nervous system of GHRKO mice and its WT counterparts(262).…”
Section: Cognitive Studies With Ghrko Micementioning
confidence: 99%
“…The chicken growth hormone is widely known as a major hormone that acts directly on chicken development and metabolism (Kim, 2010) and relates to egg production (Su et al, 2014;Vu & Ngu, 2016). GH regulates a variety of physiological functions such as growth, body composition, egg production, aging, reproduction, sexual maturation, and functionality of the central nervous system (Gosney et al, 2012;Hrabia et al, 2008;Hull & Harvey, 2014;Stephen et al, 2001). The GH/ IGF-1 signaling pathway is also believed to be capable of promoting growth of selected types of cancer (Kopchick et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in the development of a dry powder nasal formulation of hGH (CP024) ( 23 ). A variety of species has been shown to express GH and GH receptors in multiple tissues in the central nervous system such as the thalamus, hypothalamus, pituitary, and hippocampus, which implicates a role for GH signaling in the development and maintenance of neural tissue as well as cognition and memory ( 24 ) Furthermore, the regulation of GH synthesis and secretion is complex and involves modulation by both central and peripherally derived modulators ( 25 ) We hypothesized that the proximity of the pituitary gland and its blood supply to the site of absorption, the potential for direct nose to brain delivery of hGH with the possibly of reaching hGH receptors in the brain, and the potential for a more physiologically equivalent hGH plasma profile ( 26 , 27 ) could make the nasal route of delivery particularly promising for GH replacement therapy. After the completion of a preclinical safety assessment package on both CriticalSorb and CP024, the current studies evaluated the safety and tolerability, pharmacokinetics, and pharmacodynamics of single and multiple doses of CP024 in healthy volunteers.…”
mentioning
confidence: 99%